Predictive significance of residual ischemia proved by dobutamine stress: Echocardiography test in patients early after the first uncomplicated myocardial infarction - Karanović Nevena; Todorović Lazar; Perišić Zoran; Pavlović Milan (Vojnosanitetski Pregled, 2004)
Background. To evaluate the long-term prognostic value of dobutamine stress-echocardiography (ECG) test for new coronary events (new episodes of angina pectoris, cardiac-related deaths, and reinfarctions) early after the first uncomplicated myocardial infarction. Methods. Dobutamine stress-echocardiography tests were performed in all of 104 patients 10-20 days after the first myocardial infarction. Patients were followed-up for 36 (29 ± 7) months. Kaplan-Meier cumulative survival curves were tested by Breslow test (Log Rank). Results. Two cardiac deaths (1.92%), nine nonfatal myocardial infarctions (8.65%), and three cases of recurrent angina pectoris (2.88%) occurred during the prospective follow-up. Cumulative survival curves showed that in patients with negative findings of dobutamine stress-echocardiography test, survival time without significant events was 35.31 months, while in the group with positive findings of dobutamine stress-echocardiography test it was 30.91 months (log Rank 7.22; p<0.01). Prognostic value of dobutamine stress-echocardiography test was analyzed by Cox regression model and was 2.92, meaning that the risk of significant events was 2.92 times higher in the group of patients with positive findings of dobutamine stress-echocardiography test. Conclusion. Patients with negative findings of dobutamine stress-echocardiography test were with significantly higher possibility of surviving without significant events in comparison with the patients in whom the findings of dobutamine stress-echocardiography test were positive. In combination with clinical signs and ECG results, the results of dobutamine stress-echocardiography test improved prognostic value in the patients with the first uncomplicated myocardial infarction, and in that way influenced the strategy of their further treatment.